Towards highly efficient solar-driven interfacial evaporation for desalination. Issue 35 (26th August 2020) - Liu, Xinghang; Mishra, Debesh Devadutta; Wang, Xianbao; Peng, Hongyan; Hu, Chaoquan
Abstract : This review systematically discusses the whole process of solar-driven interfacial desalination and the critical issues involved from the perspective of energy flow. Abstract : Conventional desalination technologies play a central role in alleviating the crisis of increasing freshwater shortages; however, they are impeded by high cost, intensive energy consumption and environmental pollution. Solar-driven interfacial evaporation (SDIE) for desalination has been recognized as one of the most promising alternatives to conventional desalination technologies for years, owing to its high evaporation efficiency induced by heat localization, sustainability and low cost. In this review, we comprehensively analyze the critical issues involved in solar-driven interfacial desalination from the energy flow perspective in light of the progress in state-of-the-art research, including photothermal conversion mechanisms and the regulation of light absorption, as well as the thermal management, water transport, salt rejection and vapor condensation of the system. In addition, we also discuss how to improve the evaporation rate above the theoretical limit and the additional electricity generation. Finally, we put forward obstacles between the theoretical research and the practical application, which we should overcome.